SANTAYANA, George (2020). Ensayos de la historia de la filosofía. Traducción de Daniel Moreno Moreno. Madrid: Tecnos. 392 páginas. - Tutor, Andrés (Daimon Revista Internacional de Filosofia, 2022)
Reseña del libro: SANTAYANA, George (2020). Ensayos de la historia de la filosofía. Traducción de Daniel Moreno Moreno. Madrid: Tecnos. 392 páginas.